Pengaruh Penerapan Model Pembelajaran Problem Based Learning terhadap Kecakapan Problem Solving Peserta Didik Kelas VIII di Pasraman Amrta Jati Cinere - Ida Ayu Putu Nopi Anggraini; I Ketut Ulianta; Made Awanita (Jurnal PASUPATI, 2020)
This study aims to determine the Effect of Problem Based Learning Models aplications on Problem Solving Skills of Class VIII Students in Pasraman Amrta Jati Cinere. The research used a quantitative approach method by using the semi-experimental method (quasi experimental design) and the nonequivalent control group design model. The data analysis techniques used the Paired Sample T-Test and Independent Sample T-Test. Based on the results of the study, it was noted that the results of the Independent Sample T-Test Test used to determine the difference in the average value of the problem solving skills of the experimental class and the control class the value of sig was obtained. (2-tailed) is 0,000 < 0.05 then H0 was successfully rejected and Ha wad accepted, it means that the variant of the posttest results of students' problem solving skills between the experimental class using the problem based learning model and the control class using the direct learning model is there significant differences. It is concluded that there is an influence of the application of the Problem Based Learning model to the problem solving skills of gradeVIII students in Pasraman Amrta Jati Cinere.Keywords: Problem Based Learning (PBL) Learning Model, Problem Solving Skills